Legal and Social Impact of the Community on the Suspension of Waqf Land Executions: A Study of Balung Tombs - Rizqia, Inki; Usman, Suparman; Dwisvimiar, Inge (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
The Cilegon Religious Court suspended the enforcement of the Supreme Court's decision number 185 K/Ag/2020, which has permanent legal force (res judicata/inkracht van gewijsde). This proves that it is difficult for the public to obtain justice due to the lengthy legal process. This study aims to determine the legal and social impact of the community on the suspension of execution and to explain the community's efforts to obtain rights to the waqf land of the Balung tomb. This type of research uses normative-empirical law through a case study approach. Sources of data used were primary data and secondary data with data collection techniques from interviews and literature studies, which were analysed qualitatively. The findings of the research show that: (1) The legal and social impact of the community on the suspension of enforcement to the waqf land of the Balung tomb , because in the cassation decision number 185 K/Ag/2020, stated the waqf pledge deed number W2/238/02/Year 2013, which became the basis for managing the land for the Balung tombs and making certificates (land books) was declared no longer valid, so there was no guarantee of certainty regarding the status of the Balung tomb as land replacement land for tombs waqf owned by the community. On the other hand, there is a social impact on the community in terms of material and immaterial losses. (2) The community's efforts to obtain land rights to replace the community's waqf graves have been made through the judiciary, government, and waqf related agencies in cilegon city, but no resolution has been reached. the respondent of the execution remains in control of all the objects of execution.